No correlation is suggested
Y⁴ + 12y² + 36
Now factorize the expression
y⁴ + 6y² + 6y² + 36
= y²(y² + 6) + 6(y² + 6)
= (y² + 6) (y² + 6)
<span>Now 6 is not the perfect square and according to rule, binomial can not be factored as the difference of two perfect squares.
</span>so multiply both.
(y² + 6)² is the answer.
(f∘g)(x) = f(g(x)) = f(x +2)
= 2(x +2) -1
= 2x +3 . . . . . selection D
Answer:
a = 16
Step-by-step explanation:
6 = a/4 + 2
4 = a/4 Subtract 2 from both sides
16 = a Multiply 4 to both sides